2021
DOI: 10.1177/2472555220979579
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Vaccine Options for COVID-19: Status after Six Months of the Disease Outbreak

Abstract: An outbreak of the coronavirus disease 2019 (COVID-19) caused by an infection of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurred in Wuhan, China, in December 2019. This new virus belongs to the group of enveloped RNA beta-coronaviruses. Symptoms may differ in various infected persons, but major presentations include dry cough, nasal congestion, shortness of breath, fever, and general malaise. The disease appears to be more severe in patients above the age of 60 years and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 122 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Vaccines prevent the spread of viral infection and reduce its mortality (4). In December 2020, the US Food and Drug Administration (FDA) introduced two mRNA vaccines produced by Pfizer and Moderna as the first COVID-19 vaccines, followed by Johnson & Johnson's adenovirus vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines prevent the spread of viral infection and reduce its mortality (4). In December 2020, the US Food and Drug Administration (FDA) introduced two mRNA vaccines produced by Pfizer and Moderna as the first COVID-19 vaccines, followed by Johnson & Johnson's adenovirus vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Especially during the COVID-19 pandemic like today [9]. Therefore, Scientists are racing against time to provide vaccinations proven to be effective [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, while differences were observed in the administration of hydroxychloroquine or corticosteroids among those with baseline high or low NT-proBNP values, subsequent studies have revealed that the use of hydroxychloroquine in the acute phase does not reduce mortality [ 33 34 ], nor do corticosteroids benefit non-severe patients [ 33 , 35 ]. As a result, their widespread use is no longer recommended.…”
Section: Discussionmentioning
confidence: 84%
“…High hs-cTnT levels in the acute phase of COVID-19 have been associated with worse long-term prognosis [ 14 , 33 ] but there is limited data on the potential association between NT-proBNP levels in the acute phase and long-term prognosis. Our findings indicate that high NT-proBNP levels may be able to identify patients with a high risk of complications both during and after hospitalization for COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%